The company man eaudiobook - Bennett, Robert Jackson (Recorded Books Inc., 2012)
Robert Jackson Bennett's debut novel Mr. Shivers was called "compelling and truly horrifying" (Library Journal), winning him favorable comparisons to Stephen King and Cormac McCarthy. The Company Man takes listeners on a wild ride to 1919 Washington state, where a war is brewing between the McNaughton Corporation and its union workers. When the conflict's latest casualty prompts McNaughton security officer Cyril Hayes to investigate, he's soon caught up in worker claims that the corporation's machines have minds of their own.